Synthesis of carbon nanomaterials using chemical vapor deposition technique for liquid adsorption - Abdul Halif, Norzilah (2011)
The synthesis of Carbon Nanotubes (CNTs) and Helical Carbon Nanofibers (HCNFs) using Floating Catalyst-Chemical Vapor Deposition method (FC-CVD) is reported. Acetone and ethanol are used as carbon sources, hydrogen as carrier gas, argon as purging gas and ferrocene as catalyst. The effect of carbon sources (acetone and ethanol), reactor temperatures (600-1000°C), and hydrogen flow rate (50 – 400 mL/min) are investigated. The CNMs produced are characterized by Thermo Gravimetrical Analysis (TGA), elemental analysis, Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) and textural analysis. The optimum condition achieved for synthesizing high yield and high purity of CNTs and HCNFs are at reactor temperature of 700°C and hydrogen flow rate of 100 mL/min and 150 mL/min, respectively. For CNTs, the highest yield obtained is 9 g carbon produced/g catalyst with the percentage purity of 92.49%. On the other hand,the highest yield achieved for HCNFs is 7 g carbon produced/g catalyst with the percentage purity of 90.63%. Increasing of temperatures and hydrogen flow rates indicates the decreasing in the surface area and the pore volume of CNTs and HCNFs. The maximum BET specific surface area and the pore volume obtained for CNTs are 90 m2/g and 0.509 cm3/g, respectively. Meanwhile, for HCNFs, the highest BET specific surface area and the pore volume achieved for CNTs are 89 m2/g and 0.1927 cm3/g, respectively. Acid and heat modification affects the BET specific surface area negatively. Nonetheless, HNO3 modification improves the oxygen functional groups but in contrary, heat modification reduces the functional groups on the surface of CNTs and HCNFs. Performance of CNTs and HCNFs are evaluated using the Methylene Blue (MB) and phenol adsorption. The equilibrium adsorption data of MB and phenol on the assynthesized CNTs and as-synthesized HCNFs are investigated. The as-synthesized HCNFs show the highest adsorption capacity for MB and phenol at room temperature with the value of 33.17 mg/g and 11.33 mg/g, respectively. The Redlich-Peterson isotherm model fitted the experimental data as it has the highest R2 and lowest SSE value. The kinetics of MB adsorption onto CNTs and HCNFs at different initial concentrations fitted the pseudo-second order model which provides the best correlation of the data. The MB and phenol adsorption isotherms at room temperature show that the acidmodified CNMs has the lowest adsorption capacity, resulting from the reduction in their BET specific surface area and the existence of surface oxygen functional groups in abundance. However, heat-modified CNMs have the highest adsorption capacity for MB and phenol, contributed by the basicity surface, in spite of their low surface area. The adsorption capacity of MB and phenol onto acid-modified CNMs decreased 3-9% as compared to as-synthesized CNTs. The adsorption capacities of CNMs are as follows: Heat-modified CNMs > As-synthesized CNMs > Acid-modified CNMs.